Metal Chelates as Antibacterials and Elemental Analysis of the Ligands - Dr Sunil Bhatt (Genius Journals, 2022)
Both the relationship between metal binding and chemotherapy, as well as the complexes formed by metals with one of the drug families, have been the subject of research. There has been substantial progress achieved in this area thanks to the contributions of completing species, in particular chelating compounds. According to the definition of chelating agents, they are required to have two or more electron donor groups that are capable of combining with medallion to create one or more stable ring structures with five or six members. Chelating agents are also required to be able to bind to metal ions. The work done to complete species has been of tremendous assistance to this area of study. There is abundant evidence to support the hypothesis that chelation is the primary mechanism behind the therapeutic benefits of a significant number of medical medicines, both naturally occurring and synthetically produced. Albert has conducted study on the relationship between metal binding and chemotherapy, and he has written a report on the metal complexes that may be discovered in one of the several families of medications. He differentiates between two separate categories of metal binding chemicals that both have a chemotherapeutic effect. Those that are able to function as antibacterial agents by adding a metal in sufficient significant numbers to bring about a rearrangement of bacterial meta boils, and those that are able to function as antidotes in cases of metal poisoning by removing metal ions from the tissue. Both of these types of compounds are known as metalloporphyrins. In order for metals to be effective as antibacterial agents, they need to be injected directly into the blood stream; however, this is not possible since metals are not selective and their toxicity is harmful to the host. This occurs as a result of the manner in which metals are utilised
Keywords: Metal; Chelates; Antibacterials; Ligands